The Influence of Instagram Influencers on Impulse Buying Fashion Products - Avrylia Indah Sari; Melly Prabawati; Esty Nurbaity Arrsy (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2023)
This study aims to obtain information about the influence of Instagram influencers on impulse buying of fashion products based on aspects of influencers such as expertise, trustworthiness, similarity, familiarity, and liking, as well as aspects of impulse buying that include spontaneity, strength, compulsions, and intensity; excitement and stimulation; and disregard for consequences. The research method uses a descriptive method with a quantitative approach. The sample size for this research is 90 respondents. The analytical method uses Chi-Square. The results of this study show that in influencers, the indicator with the highest influence is similarity, with a percentage of 100%. In impulse buying, the indicator with the highest influence is the indicator of excitement and stimulation, with a very high category of 78.9%. The results of the data analysis show a value of 0.00 0.05. The more significant the influence of Instagram influencers, the higher the impulse buying of fashion products. Any change in value among influencers will improve impulse buying by 5.333.